Ijtihad and the Dynamics of Islamic Legal Interpretation: An Epistemological Exploration in the Contemporary Context - Bambang (NUSANTARA: Journal Of Law Studies, 2024)
This study examines the epistemological foundation of ijtihad and its dynamic role in interpreting Islamic law in the contemporary era. As an intellectual and methodological effort, ijtihad serves as a means for scholars to derive legal rulings from the Qur’an and Sunnah in response to emerging social realities. In today’s rapidly changing world—characterized by globalization, technological innovation, and cultural diversity—traditional frameworks of Islamic jurisprudence confront new challenges that necessitate a more flexible and contextual understanding of ijtihad. Through a qualitative-descriptive approach and library-based analysis, this research explores both classical and modern perspectives on ijtihad, tracing the evolution of its epistemological basis over time. The findings indicate that contemporary ijtihad should move beyond literal and rigid interpretations by embracing rational reflection (‘aql), ethical objectives (maqasid al-shariah), and contextual reasoning. Such an approach allows Islamic law to remain faithful to its foundational sources while also being responsive to modern social, political, and ethical issues. This study concludes that revitalizing the epistemology of ijtihad is essential for addressing complex challenges in areas such as governance, human rights, bioethics, and social justice. Academically, it contributes to the renewal of Islamic legal thought by positioning ijtihad as a dynamic framework that bridges classical jurisprudence with the needs of contemporary society—promoting a vision of Islamic law that is both authentic and transformative.